A systematic review and network meta-analysis protocol of adjuvant chemotherapy regimens for resected gastric cancer. Issue 7 (February 2019) - Ge, Long; Hou, Liangying; Yang, Qingxia; Wu, Yiting; Shi, Xiue; Li, Jiang; Yang, Kehu
Abstract: Background: Gastric cancer is the third leading cause of cancer death in the world. The benefit of adjuvant chemotherapy has been demonstrated by published individual patient data meta-analysis and Cochrane systematic review. However, there is no consensus on which is the optimal adjuvant chemotherapy regimens. Present network meta-analysis aims to compare the differences of effect between all available adjuvant chemotherapy regimens in improving overall survival and disease-free survival, and to rate the certainty of evidence from present network meta-analysis. Methods: We will conduct this systematic review and network meta-analysis using Bayesian method and according to Preferred Reporting Items for Systematic review and Meta-Analysis Protocols (PRISMA-P) statement. We will search PubMed, EMBASE.com, the Cochrane Central Register of Controlled Trials (CENTRAL), Chinese National Knowledge Infrastructure (CNKI), and Chinese Biological Medical Database (CBM), and ClinicalTrials.gov (http://clinicaltrials.gov/ ) to identify randomized controlled trials (RCTs) comparing adjuvant chemotherapy to surgery alone. We will assess the risk of bias of individual RCTs using a modified version of Cochrane tool. We will also use the advance of GRADE to rate the certainty of network meta-analysis. Data analysis will be performed with R-3.4.1 and WinBUGS software. Results: The results of this study will be published in a peer-reviewed journal. Discussion: To the best of our knowledge, this systematic review and network meta-analysis will firstly use both direct and indirect evidence to compare the differences of all available adjuvant chemotherapy regimens for resected gastric cancer patients. This is a protocol of systematic review and meta-analysis, so the ethical approval and patient consent are not required.